3(x+6)+4(x+2)=12

Simple and best practice solution for 3(x+6)+4(x+2)=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+6)+4(x+2)=12 equation:


Simplifying
3(x + 6) + 4(x + 2) = 12

Reorder the terms:
3(6 + x) + 4(x + 2) = 12
(6 * 3 + x * 3) + 4(x + 2) = 12
(18 + 3x) + 4(x + 2) = 12

Reorder the terms:
18 + 3x + 4(2 + x) = 12
18 + 3x + (2 * 4 + x * 4) = 12
18 + 3x + (8 + 4x) = 12

Reorder the terms:
18 + 8 + 3x + 4x = 12

Combine like terms: 18 + 8 = 26
26 + 3x + 4x = 12

Combine like terms: 3x + 4x = 7x
26 + 7x = 12

Solving
26 + 7x = 12

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-26' to each side of the equation.
26 + -26 + 7x = 12 + -26

Combine like terms: 26 + -26 = 0
0 + 7x = 12 + -26
7x = 12 + -26

Combine like terms: 12 + -26 = -14
7x = -14

Divide each side by '7'.
x = -2

Simplifying
x = -2

See similar equations:

| 6x-4-3x-3=3 | | X^2-5x-y=0 | | 3h-2=35 | | 3(X/7)=24 | | (2x+4)(5x+5)= | | 2(3x-2)-3(x+1)=3 | | (C-2)(C-5)= | | y[n]-0.5*y[n-2]=0 | | 24/2=4/2x | | 44=2(4+3x)+2(4+5x) | | 2x(x+e)=3e(x+e) | | 162=2xsquared | | 4s^2+19=12s | | x/y=2.727272 | | 10x-x^2=5 | | 10x-y^2=5 | | 3+4x-10=17 | | N(14+6)=22 | | (a+1)(a*2+3a+1)= | | x^2-61.28x=2000 | | 15+3y=51-y-y-y | | 16-7m=30 | | 5-3y+5y=-8+6+9y | | -(x-1)=x-5 | | 64-32y=55-35y | | 27=5-2x | | 7+91x=52x+3 | | -2(x-5)=10-3x | | 6x-3x(x-1)=21 | | 2x^2+2y-1=0 | | 2cosx+4sinx=3 | | 16x-5y=125 |

Equations solver categories